CONTENT VALIDITY ANALYSIS OF ENGLISH SUMMATIVE TEST BASED ON THE JUNIOR HIGH SCHOOL SYLLABUS - Kartini; Annisa Shofa Tsuraya; Syahrullah (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2022)
The objective of this research is to find the empirical evidence of the English summative test administered to the students for the seventh grade at Junior High School of Unismuh Makassar that is appropriate with the indicators of reading and writing skills in the English syllabus and has good content validity. The method of this research is descriptive research. The data was collected by observing and analyzing the English summative test. To know the content validity of the test, this research used the comparative analytic method, that is, by comparing the contents of the test with the English syllabus focusing on reading and writing indicators. The finding of the research was that the test items in the English summative test in the odd semester for the seventh grade students of Junior High School of Unismuh Makassar were appropriate with the recommended indicators in reading and writing skills in the English syllabus. They cover 11/18 x 100% = 61.11%. This percentage obviously falls into the level of 56%-75%, which means sufficient. This research proved that items of the English summative test for the odd semester of the seventh grade students in the Junior High School of Unismuh Makassar have sufficient content validity. It showed that most of the materials of the English summative test are appropriate to the recommended English syllabus referring to reading and writing standard competence.